Fleksibilitas Interpretatif Pengguna sebagai Kelompok Sosial Relevan Situs Tanya Jawab “Quora” - I Gusti Lanang Agung Kharisma Wibhisono; Irwansyah Irwansyah (Avant Garde, 2020)
The development of internet brings out the ability of users to create and share their own contents. This phenomenon is commonly referred as user-generated content. The presence of new technology provides an opportunity for users to do various activities online such as creating blogs, networking through SNS, participating in virtual games, as well as gathering information from the internet. One form of information gathering activities is the usage of question and answer platform. In the perspective of Social Construction of Technology Theory, technological artifact development is constructed by relevant social groups. This research aims to know the interpretative flexibility of Q&A platform users as relevant social group, and the process of information construction in the platform. Through qualitative approach, this research describes the interpretative flexibility of Q&A platform users’. Informants were chosen purposively. This research suggests that users as a relevant social group demonstrates interpretative flexibility to describe Q&A platform as an artifact. Information construction happens within the Q&A practice and reflects the characteristic of user-generated content in Web 2.0.